Information sharing between mutual funds and auditors - HOPE, Ole‐Kristian (Institutional Knowledge at Singapore Management University, 2023)
This paper examines whether there is information sharing between mutual funds and their auditors about the auditors’ other listed firm clients. Using data from the Chinese market, we find that mutual funds earn higher profits from trading in firms that share the same auditors. The effects are more pronounced when firms have a more opaque information environment and when the audit partners for the fund and the partners for the listed firm share school ties. The evidence is consistent with information flowing from auditors to mutual funds, providing mutual funds with an information advantage in firms that share the same auditors. Our findings are robust to the use of audit-firm mergers and acquisitions (M&As) as exogenous shocks and several other robustness checks. We further find that auditors benefit by charging higher audit fees for mutual fund clients and by improving their audit quality for listed firm clients. Our study provides evidence of bi-directional information sharing between two important market intermediaries.